Dynamic recruitment of active proteasomes into polyglutamine initiated inclusion bodies. Issue 1 (26th November 2013) - Schipper-Krom, Sabine; Juenemann, Katrin; Jansen, Anne H.; Wiemhoefer, Anne; van den Nieuwendijk, Rianne; Smith, Donna L.; Hink, Mark A.; Bates, Gillian P.; Overkleeft, Hermen; Ovaa, Huib; Reits, Eric
Abstract : Neurodegenerative disorders such as Huntington's disease are hallmarked by neuronal intracellular inclusion body formation. Whether proteasomes are irreversibly recruited into inclusion bodies in these protein misfolding disorders is a controversial subject. In addition, it has been proposed that the proteasomes may become clogged by the aggregated protein fragments, leading to impairment of the ubiquitin–proteasome system. Here, we show by fluorescence pulse‐chase experiments in living cells that proteasomes are dynamically and reversibly recruited into inclusion bodies. As these recruited proteasomes remain catalytically active and accessible to substrates, our results challenge the concept of proteasome sequestration and impairment in Huntington's disease, and support the reported absence of proteasome impairment in mouse models of Huntington's disease. Abstract : Proteasomes are reversibly recruited to polyglutamine aggregates. Proteasomes directly interact with the polyglutamine fragments. Recruited proteasomes remain accessible to substrates. The UPS does not become impaired by polyglutamine aggregates.